1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Prove the following identity by mathematical induction

  1. Jul 11, 2008 #1
    1. The problem statement, all variables and given/known data
    Prove the following identity by mathematical induction:
    [tex]\sum_{i=1}^n \frac{1}{(2i - 1)(2i + 1)} = \frac{n}{(2n + 1)}[/tex]

    2. Relevant equations

    3. The attempt at a solution

    Let P(n) = [tex]\sum_{i=1}^n \frac{1}{(2(1) - 1)(2(1) + 1)} = \frac{1}{(2(1) + 1)}[/tex]

    P(1) = [tex]\sum_{i=1}^n \frac{1}{(1)(3)} = \frac{1}{3}[/tex] is true

    Assuming P(k) is true, then P(k + 1) is also true.

    [tex]\sum_{i=1}^n \frac{1}{(2(k + 1) - 1)(2(k + 1) + 1)} = \frac{k + 1}{(2(k + 1) + 1)}[/tex]

    Do I just change all the i's and n's to k+1 and expand it until left equation is equal to the right?
  2. jcsd
  3. Jul 11, 2008 #2
    Re: Induction

    You assume that this is true:
    [tex]\sum_{i=1}^k \frac{1}{(2i - 1)(2i + 1)} = \frac{k}{(2k + 1)}[/tex]

    And then find a way to change the above in to this:

    [tex]\sum_{i=1}^{k+1} \frac{1}{(2i - 1)(2i + 1)} = \frac{k+1}{(2(k+1) + 1)}[/tex]

    Notice how I made the replacement everywhere.
  4. Jul 11, 2008 #3


    User Avatar
    Homework Helper

    Re: Induction

    The expression you have there doesn't make sense. The summation is for an index of i, yet k is used. Replacing i with k would still be incorrect. Instead, find a way to write [tex]\sum^{k+1}_{k=0} \frac{1}{(2k+1)(2k-1)} \ \mbox{in terms of} \ \sum^{k}_{k=0} \frac{1}{(2k+1)(2k-1)} \ \mbox{and the (k+1)th summand}[/tex] and then use the induction assumption.

    PS. Avoid using "i" when you are not working with complex numbers. It gets confusing after a while.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook